A Quality Scorecard for the era of Industry 4.0. (29th July 2018) - Shin, Wan Seon; Dahlgaard, Jens J.; Dahlgaard-Park, Su Mi; Kim, Min Gyu
Abstract : A Quality Scorecard (QSC) performance measurement model is proposed to evaluate the quality aspects of an organization in Industry 4.0. To design a QSC for the 'Fourth Industrial Revolution', we examined existing measures regarding costs of quality items. The measurement system was refined by simplifying duplicate measures and incorporating quality elements considered in recent international standard revisions. This paper explains the QSC system and its practical use. Two key results were obtained. First, the QSC measures were reduced from a total of 139 potential measures to 15, 30, and 60 for simple, general, and detailed models, respectively. Second, a so-called QSC wheel, a virtual tool to assess weaknesses in existing performance measurement systems, was developed. The QSC wheel may effectively be used in analysing existing performance measurement systems, and may also be applied to evaluate qualitative performance levels in Industry 4.0.